Which Beta Is Best? On the Information Content of Option‐implied Betas. (17th August 2015) - Baule, Rainer; Korn, Olaf; Saßning, Sven
Abstract: Option‐implied betas are a promising alternative to historical beta estimators, because they are inherently forward‐looking and can incorporate new information immediately and fully. Recently, different implied beta estimators have been developed, but very little is known about their properties and information content. This paper presents a first systematic comparison between six different implied beta estimators, providing guidance for applications and identifying directions for further improvement. The analysis identifies explanatory factors for the predictive performance of implied estimators both in the cross section of stocks and over time. Furthermore, the analysis reveals patterns in the term structure of implied betas.